2022
DOI: 10.1155/2022/5126042
|View full text |Cite
|
Sign up to set email alerts
|

Xuesaitong Combined with Dexmedetomidine Improves Cerebral Ischemia-Reperfusion Injury in Rats by Activating Keap1/Nrf2 Signaling and Mitophagy in Hippocampal Tissue

Abstract: Ischemic stroke is the most common type of cerebrovascular disease with high mortality and poor prognosis, and cerebral ischemia-reperfusion (CI/R) injury is the main murderer. Here, we attempted to explore the effects and mechanism of Xuesaitong (XST) combined with dexmedetomidine (Dex) on CI/R injury in rats. First, a rat model of CI/R injury was constructed via the middle cerebral artery occlusion (MCAO) method and treated with XST and Dex alone or in combination. Then, on the 5th and 10th days of treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Numerous studies have shown that Dex has protective effects on heart, kidney, lung and other organs in ischemia-reperfusion animal models [ 34 ]. It has been found that Dex plays a protective role in intestinal ischemia-reperfusion injury through anti inflammation, inhibition of caspase-3 protein expression and apoptosis [ 35 ]. It was reported that Dex could attenuate neuronal injury induced by cerebral ischemia-reperfusion by regulating miR-199a [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that Dex has protective effects on heart, kidney, lung and other organs in ischemia-reperfusion animal models [ 34 ]. It has been found that Dex plays a protective role in intestinal ischemia-reperfusion injury through anti inflammation, inhibition of caspase-3 protein expression and apoptosis [ 35 ]. It was reported that Dex could attenuate neuronal injury induced by cerebral ischemia-reperfusion by regulating miR-199a [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xuesaitong (XST), a Chinese medicinal preparation containing PNS, is widely used in the treatment of ischemic stroke. A study showed that it combined with dexmedetomidine I attenuated I/R injury by activating Keap1/Nrf2 signaling and mitophagy ( Han et al, 2022b ).…”
Section: Regulation For Management Of Cerebral I/r Injurymentioning
confidence: 99%
“…Animal and cellular experiments have further demonstrated that CHM monomers and decoctions can improve ischemic stroke symptoms and provide neuroprotection by attenuating cerebral I/R injury ( Ding et al, 2019 ; Jiao-Yan et al, 2021 ; Tang et al, 2021 ; Ni et al, 2022 ; Liao et al, 2023 ). These studies have found that many Chinese medicines, including monomers and decoctions, can attenuate cerebral I/R injury by modulating mitophagy ( Zhang et al, 2020a ; Han et al, 2022a ; Ji et al, 2022a ; Huang et al, 2023a ). Interestingly, some of these medicines work by inhibiting mitophagy, while others work by activating it.…”
Section: Introductionmentioning
confidence: 99%
“…The hippocampus is an essential limbic system and irreplaceable in learning, memory and cognitive function. The hippocampus is susceptible and easily damaged in cerebral ischemia, the central part of histopathological changes induced by cerebral ischemia [9]. Nuclear factor E2-related factor2 (Nrf2) can alleviate the progression of neurodegenerative diseases by regulating antioxidant defence, improving mitochondrial function, inhibiting in ammatory damage and other bene cial effects [10].…”
Section: Introductionmentioning
confidence: 99%